Quantitative Analysis of Sex-Hormone-Binding Globulin Glycosylation in Liver Diseases by Liquid Chromatography–Mass Spectrometry Parallel Reaction Monitoring - Yuan, Wei (J Proteome Res, 2018)
Sex-hormone-binding globulin (SHBG) is a liver-secreted glycoprotein and a major regulator of steroid distribution. It has been reported that the serum concentration of SHBG changes in liver disease. To explore the involvement of SHBG in liver disease of different etiologies in greater detail, we developed a sensitive and selective liquid chromatography–mass spectrometry parallel reaction monitoring workflow to achieve quantitative analysis of SHBG glycosylation micro heterogeneity. The method uses energy-optimized “soft” fragmentation to extract informative Y ions for maximal coverage of glycoforms and their quantitative comparisons. A total of 15 N-glycoforms of two N-glycosites and 3 O-glycoforms of 1 O-glycosite of this low-abundance serum protein were simultaneously analyzed in the complex samples. At the same time, we were able to partially resolve linkage isoforms of the fucosylated glycoforms and to identify and quantify SHBG N-glycoforms that were not previously reported. The results show that both core and outer-arm fucosylation of the N-glycoforms increases with liver cirrhosis but that a further increase of fucosylation is not observed with hepatocellular carcinoma (HCC). In contrast, the α-2–6 sialylated glycoform of the O-glycopeptide of SHBG increases in liver cirrhosis, and a significant 2-fold further increase is observed in HCC. In general, we do not find a significant contribution of different liver disease etiologies to the observed changes in glycosylation; however, elevation of the newly reported HexNAc(4)Hex(6) N-glycoform is associated with alcoholic liver disease.